Very short, fairly interesting and reasonably cheap book about qualitative research - Silverman, David (Sage Publications Ltd, New Delhi, 2013)
The Second Edition of Qualitative Research provides a refreshing introduction to doing and debating qualitative research. The author uses updated content, ranging from photographs to novels and newspaper stories, to demonstrate how getting to grips with qualitative methods means asking ourselves fundamental questions about how we are influenced by contemporary culture. Conceived by Chris Grey as an antidote to conventional textbooks, each book in the 'Very Short, Fairly Interesting and Reasonably Cheap' series takes a core area of the curriculum and turns it on its head by providing a critical and sophisticated overview of the key issues and debates in an informal, conversational and often humorous way. Suitable for Undergraduate students who are new to qualitative research and even Postgraduates and Practitioners who want re-assess their current understanding of the field.
Includes bibliographical references (p. 162-172) and index.
Keywords: Qualitative research; Research methodology; Social sciences; Critical thinking; Academic textbooks